Digitalisasi Desa Mandiri - Saputra, Arie; Syahril, Syahril; fitriadi, fitriadi; Hadi, Khairul; Harmaini, Harmaini (Jurnal Pengabdian Agro and Marine Industry, 2024)
The digital era has brought significant changes in various aspects of life, including in rural areas. Digitalization of Independent Villages emerged as a solution to encourage village independence through the use of digital technology. The main aim of this digitalization is to improve the quality of life of village communities, improve access to public services, and encourage local economic growth. This article discusses various important aspects of the Mandiri Village digitalization program, including development of technological infrastructure, development of village information systems, digital literacy training, and digital marketing for local products. The implementation of digitalization in Leukeun Village has shown positive results, such as improving technological infrastructure, efficiency of public services, empowering the local economy, and increasing community digital literacy. Despite facing challenges such as limited funding and low digital literacy, collaboration with external parties and sustainable development strategies can overcome these obstacles. Digitalization of Mandiri Village is not just the application of technology, but also creates positive and sustainable changes for village communities. This article aims to develop Leukeun Mandiri Village based on digital concepts by considering internal and external potential through inclusive and integrated solutions.